2023
DOI: 10.17221/441/2022-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulants improves the content of polyphenol in the potato tubers

Abstract: In recent years, a marked increase in the interest in and application of raw materials and plant products in nutrition and prophylaxis of numerous medical conditions has been observed. Such plants include potatoes, the world's fourth most important staple food. In nutritional terms, potato is a rich source of carbohydrates, protein, minerals and vitamins; also, it is available all year round (Leszczyński 2012, Akyol et al. 2016. The crop contains valuable bioactive compounds desirable in the human diet (Mishra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It is possible that the N that was provided via the biostimulants to the potato plants resulted in an increase in the yield, while the herbicide mechanism of action did not disrupt the biostimulant's action. This combination of biostimulants and herbicides was also found to enhance polyphenol content in potato tubers [39] but interestingly decreased glycoalkaloid concentration [40]. In an experiment that utilized the application of the three aforementioned biostimulants to evaluate the possibility of a profitable implementation in potatoes, it has been found that the addition of biostimulants at BBCH 13-19 (first application) and BBCH 31-35 (second application) raised yield significantly, compared to just mechanical (16-26%) and chemical (clomazone + metribuzin) weeding (up to 13%) [41].…”
Section: Interaction Effects On Biostimulant and Herbicidal Efficacymentioning
confidence: 89%
“…It is possible that the N that was provided via the biostimulants to the potato plants resulted in an increase in the yield, while the herbicide mechanism of action did not disrupt the biostimulant's action. This combination of biostimulants and herbicides was also found to enhance polyphenol content in potato tubers [39] but interestingly decreased glycoalkaloid concentration [40]. In an experiment that utilized the application of the three aforementioned biostimulants to evaluate the possibility of a profitable implementation in potatoes, it has been found that the addition of biostimulants at BBCH 13-19 (first application) and BBCH 31-35 (second application) raised yield significantly, compared to just mechanical (16-26%) and chemical (clomazone + metribuzin) weeding (up to 13%) [41].…”
Section: Interaction Effects On Biostimulant and Herbicidal Efficacymentioning
confidence: 89%